ANALISIS YURIDIS PERKAWINAN DIBAWAH UMUR PASCA BENCANA GEMPA, TSUNAMI DAN LIKUIFAKSI DI KABUPATEN SIGI SULAWESI TENGAH - Patiscawaty, Roslinda; Supryadi; Sitti Fatimah Maddulisa (Universitas Tadulako, 2024)
Underage marriage is a marriage carried out by a man and a woman where the ages of both are still below the minimum limit regulated by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage and the prospective bride and groom. They are not ready physically or mentally, and the bride and groom are not yet mentally mature and there is also the possibility that they are not ready in material terms. For this reason, this research aims to determine the factors and impacts of child marriage in Sigi Regency, after the disaster. The research method the author uses is empirical juridical. The results of this research are the factors that cause child marriage in Sigi Regency after the earthquake, namely pre-wedding pregnancy, environment, economy, parents/family, education, culture or tradition and mass media. The impact of underage marriage due to disasters is (1) positive impact: avoiding adultery and reducing the burden on parents. (2) negative impact: psychological maturity has not been achieved, children's rights are not fulfilled, health impacts, increasing divorce rates, and lower living standards. low. This research recommends that minors who decide to marry at an early age are expected to think carefully about their decision before deciding to marry, because building a marriage requires a lot of preparation, both physical, psychological and financial. If you finally decide to get married, it is hoped that you have prepared everything carefully so that the quality of life after marriage is better than before marriage.